Development of a bivalent conjugate vaccine candidate against rotaviral diarrhea and tuberculosis using polysaccharide from Mycobacterium tuberculosis conjugated to ΔVP8* protein from rotavirus. Issue 45 (29th October 2021) - Park, Wook-Jin; Yoon, Yeon-Kyung; Kim, Youngmi; Park, Ji-Sun; Pansuriya, Ruchirkumar; Cho, Sang-Nae; Seok, Yeong-Jae; Ganapathy, Ravi
Abstract: Conjugation of carbohydrate antigens with a carrier protein is a clinically proven strategy to overcome the poor immunogenicity of bacterial polysaccharide. In addition to its primary role, which is to help generate a T cell-mediate long-lasting immune response directed against the carbohydrate antigen, the carrier protein in a glycoconjugate vaccine can also play an important role as a protective antigen. Among carrier proteins currently used in licensed conjugate vaccines, non-typeable Haemophilus influenzae protein D has been used as an antigenically active carrier protein. Our previous studies also indicate that some carrier proteins provide B cell epitopes, along with T cell helper epitopes. Herein we investigated the dual role of truncated rotavirus spike protein ΔVP8* as a carrier and a protective antigen. Capsular polysaccharide lipoarabinomannan (LAM), purified from Mycobacterium tuberculosis (M.tb), was chemically conjugated with ΔVP8*. Mouse immunization experiments showed that the resultant conjugates elicited strong and specific immune responses against the polysaccharide antigen, and the responses were comparable to those induced by Diphtheria toxoid (DT)-based conjugates. The conjugate vaccine induced enhanced antibody titers and functional antibodies against ΔVP8* when compared to immunization with the unconjugated ΔVP8*. Thus, these results indicate that ΔVP8* can be a relevant carrier protein for glycoconjugate vaccine and the glycoconjugates consisting of ΔVP8* with LAM are effective bivalent vaccine candidates against rotavirus and tuberculosis.